Sulfasalazine as an Immunomodulator of the Inflammatory Process during HIV-1 Infection. (2019)
HIV-1 induces an uncontrolled inflammatory response of several immune components, such as inflammasomes. These molecular complexes, associated with Toll-like receptor (TLR) activity, induce the maturation and release of IL-1 and IL-18 and eventually induce pyroptosis. It has been previously demonstrated that HIV induces inflammasome activation, which is significantly lower in the gastrointestinal tissue and blood from people living with HIV-1 with spontaneous control of viral replication. Therefore, immunomodulatory agents could be useful in improving HIV prognosis.